Meningkatkan Pemahaman Siswa pada Materi Perkembangbiakan pada Tumbuhan Melalui Pembelajaran Kooperatif dan Media Gambar pada Peserta Didik Kelas IX B SMP Negeri 2 Kumai Tahun Pelajaran 2019/2020: Improving Student Understanding of Plant Reproduction Materials Through Cooperative Learning and Picture Media for Class IX B Students at SMP Negeri 2 Kumai for the Academic Year 2019/2020 - Sumedi, Sumedi (Anterior Jurnal, 2022)
In semester 1, class IX students learn about plant reproduction. One of the characteristics of life is to reproduce as a goal to produce offspring. This is also done by plants. In general, there are two types of plant reproduction, namely generative and vegetative reproduction. The learning carried out in class IX of SMP Negeri 2 Kumai is not very conducive, it causes students' low understanding of reproduction in plants. Many students cannot understand the material. Based on the description in the previous chapter, the researcher concludes from the results of research conducted at SMP Negeri 2 Kumai that there is an increase in understanding of plant reproduction in Class IX of SMP Negeri 2 Kumai in students' understanding of plant reproduction. In the pre-cycle 8 students who finished learning, then increased in cycle 1 there were 22 students who finished learning and in cycle 2 it reached 27 students. The average value showed in the pre-cycle was 68.23, then increased to 78.92 in cycle 1 and became 81.92 in cycle 2. So the research with the problem "Improving Student Understanding About Reproduction in Plants Through Cooperative Learning and Picture Media in Classroom IX SMP Negeri 2 Kumai for the academic year 2019/2020" in the process and a period of time that is not short, cooperative learning and image media have a positive impact on students, namely class IX students can increase students' understanding of reproduction in plants.